1990
DOI: 10.1111/j.1600-9657.1990.tb00401.x
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of light‐cured composite resin to bleached and unbleached bovine dentin

Abstract: Cylinders of small‐particle light‐cured composite resin were bonded to the superficial dentin layer of young bovine incisors that had previously been subjected to 4 different treatments: 1) immersed in 35% hydrogen peroxide for 60 min, then etched with 37% phosphoric acid gel for 60 s; 2) immersed in saline for 60 min, then etched with 37% phosphoric acid gel; 3) etched with 37% phosphoric acid gel for 60 s, then immersed in 35% hydrogen peroxide for 60 min; and 4) etched with 37% phosphoric acid gel, then imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
0
6

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 8 publications
5
47
0
6
Order By: Relevance
“…The results revealed that the exposure of dentin to peroxide decreased the bond strength, as reported in several previous studies [15,16,23,27] (Table 1).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results revealed that the exposure of dentin to peroxide decreased the bond strength, as reported in several previous studies [15,16,23,27] (Table 1).…”
Section: Discussionsupporting
confidence: 87%
“…It has been reported that allowing a one-week period between bleaching and restorative treatment reversed the enamel bond strength [2]. However, this method was not effective for bleached dentin [23,27].…”
Section: Introductionmentioning
confidence: 99%
“…O nível de desenvolvimento e maturidade do dente pode ser considerado uma dessas variáveis, a qual pode ser padronizada pela faixa etária já que os dentes são conseguidos de animais que normalmente são sacrificados numa mesma idade 7 . A literatura 8,9 recomenda o uso de dentes de animais jovens que tenham até quatro incisivos permanentes erupcionados obtidos da região labial onde há pouca ou nenhuma deterioração.…”
Section: Discussionunclassified
“…Com o intuito de encontrar substitutos para os dentes humanos em testes para novos materiais, os dentes bovinos têm sido largamente utilizados, principalmente para se comparar o resultado na utilização de materiais odontológicos 2,12 . Os materiais dentários precisam ser testados in vitro antes de sua aplicação clínica 7,9 . Entretanto, tem se tornado bastante difícil obter dentes extraídos humanos sem cárie em número suficiente para estes estudos.…”
unclassified
See 1 more Smart Citation